Mechanisms of offshore solid and liquid freshwater flux from the East Greenland Current - Spall, Michael A.; Semper, Stefanie; Våge, Kjetil (Journal of Physical Oceanography, 2024)
The mechanisms that control the export of freshwater from the East Greenland Current, in both liquid and solid form, are explored using an idealized numerical model and scaling theory. A regional, coupled ocean–sea ice model is applied to a series of calculations in which key parameters are varied and the scaling theory is used to interpret the model results. The offshore ice flux, occurring in late winter, is driven primarily by internal stresses and is most sensitive to the thickness of sea ice on the shelf coming out of Fram Strait and the strength of alongshore winds over the shelf. The offshore liquid freshwater flux is achieved by eddy fluxes in late summer while there is an onshore liquid freshwater flux in winter due to the ice–ocean stress, resulting in only weak annual mean flux. The scaling theory identifies the key nondimensional parameters that control the behavior and reproduces the general parameter dependence found in the numerical model. Climate models predict that winds will increase and ice export from the Arctic will decrease in the future, both of which will lead to a decrease in the offshore flux of sea ice, while the influence on liquid freshwater may increase or decrease, depending on the relative changes in the onshore Ekman transport and offshore eddy fluxes. Additional processes that have not been considered here, such as more complex topography and synoptic wind events, may also contribute to cross-shelf exchange. publishedVersion